Changes in prevalence and perinatal outcomes of congenital hydrocephalus among Chinese newborns: a retrospective analysis based on the hospital-based birth defects surveillance system - Ling Yi; Chaomin Wan; Changfei Deng; Xiaohong Li; Kui Deng; Yi Mu; Jun Zhu; Qi Li; Yanping Wang; Li Dai (BMC, 2017)
Abstract Background Little is known about the epidemiology of congenital hydrocephalus (CH) in China. This study aimed to depict recent changes in CH prevalence and perinatal outcomes of the affected newborns. Methods Data were obtained from the Chinese Birth Defects Monitoring Network (CBDMN), which collects demographic information on all newborns above 28 weeks of gestation, and clinical information on neonates with congenital anomalies. CH cases delivered during 2005-2012 were analyzed. Poisson regression was used to calculate prevalence ratios (PR) and 95% confidence intervals, and linear chi-square test was used to examine time trend of CH prevalence. Results Five thousand two hundred forty-five isolated and 1245 associated CH cases were identified among 10,574,061 newborns, yielding the prevalence of 4.96, 1.18 and 6.14 per 10,000 births for the isolated, associated and overall hydrocephalus, respectively. The annual prevalence of CH presented a decreasing trend (from 7.52 to 5.98 per 10,000 births, P < 0.001). Higher prevalence was found in both younger (<20 years, PR: 1.81, 95% CI: 1.56-2.10) and older (≥35 years, PR: 1.48, 95% CI: 1.36-1.61) maternal-age groups in comparison with the maternal-age group of 20 to 24 years. Higher prevalence was also found in infants born to mothers resided in rural areas, male infants, and multiple births. Of non-aborted infants with congenital hydrocephalus, 38.11% were born with low birth weight, 37.53% were preterm birth, and 20.69% died within 7 days after birth. Conclusions Our findings present a relatively high prevalence and poor perinatal outcomes of CH in China, which can serve as a baseline for future study.